Amplified Spontaneous Green Emission and Lasing Emission From Carbon Nanoparticles. (27th December 2013) - Qu, Songnan; Liu, Xingyuan; Guo, Xiaoyang; Chu, Minghui; Zhang, Ligong; Shen, Dezhen
<x xml:space="preserve">Abstract</x> In this work, the optical properties of carbon nanoparticles (CNPs) can be modulated by the dopant‐N atom and sp2 C‐contents. CNPs prepared with the low urea mass ratio of 0.2:1 (CNP1) exhibit blue emission (maximum PL quantum yield: 15%). Increasing sp2 C‐ and dopant‐N atom contents, as determined in CNPs prepared with high urea mass ratio of 2:1 (CNP2), lead to green emission (maximum PL quantum yield up to 36% in ethanol aqueous solution). Amplified spontaneous emission (ASE) can be observed only in CNP2 ethanol aqueous solution. Green lasing emission is achieved from CNP2 ethanol aqueous solution in a linear long Fabry‐Perot cavity, indicating the potential of CNP2 as a gain medium for lasing. CNP2 shows superior photostability compared with C545T dye. The green emission from CNP2 is speculated to arise from electron‐hole recombination (intrinsic state emission). The high PL quantum yield and small overlap between absorption and emissions of CNP2 ethanol aqueous solution are the key factors in realizing lasing emission.